2013
DOI: 10.1007/s13201-013-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fenton-based treatment of petroleum refinery wastewater with scrap iron using response surface methodology

Abstract: The ever-increasing number and production capacity of petroleum refineries in recent years have intensified the need for developing an effective and practical method for treating their wastewaters. In this study, the application of Fenton process with scrap iron powder was investigated for the treatment of a bio-refractory petroleum refinery effluent. Response surface methodology was employed with a cubic IV optimal design to optimize the process using chemical oxygen demand (COD) removal as the target respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Here, the ratios are based on mass (molar) and it was reported in many of the researchers (Bach et al 2010;Hasan et al 2012). It was proved that, the Fenton's oxidation shows better results in acidic pH from 2 to 5 (Xu et al 2004;Saber et al 2014) and 3-4 (Lucas et al 2007;Manu and Mahamood 2011). Hence, the pH values were considered as 2, 3.5 and 5.…”
Section: Experimental Designmentioning
confidence: 95%
“…Here, the ratios are based on mass (molar) and it was reported in many of the researchers (Bach et al 2010;Hasan et al 2012). It was proved that, the Fenton's oxidation shows better results in acidic pH from 2 to 5 (Xu et al 2004;Saber et al 2014) and 3-4 (Lucas et al 2007;Manu and Mahamood 2011). Hence, the pH values were considered as 2, 3.5 and 5.…”
Section: Experimental Designmentioning
confidence: 95%
“…A petrochemical residue with 450 mg L -1 of initial COD presented approximately 80% of COD removed by Fenton process. 42 Kakavandi and Babaei 43 found satisfactory COD removal for a petrochemical residue (initial COD range 50-1000 mg L -1 ) with the heterogeneous Fenton process. However, as shown in Figure 6, Fenton and photo-Fenton processes did not show satisfactory results.…”
Section: Degradation Of the Raw Liquid Residuementioning
confidence: 98%
“…The presented results showed that Fenton is a promising process to the treatment of petrochemical residue. However, considering the toxicity of the final treated residue, the association of Fenton with another treatment such as post-coagulation is worth testing, as discussed in the work of Saber et al 42…”
Section: Degradation Of the Raw Liquid Residuementioning
confidence: 99%
“…Nonetheless, high concentrations of Fe 2+ ion can only increase the rate of the reaction up to a certain limit. Exceeding the optimum concentration, the rate of degradation becomes less significant due to the scavenged radicals by Fe 2+ [43]. In addition, it can also inhibit the degradation process because Fe 2+ ions may compete with the organic pollutants to react with the •OH radicals (Eq.…”
Section: Effect Of Fe 2+mentioning
confidence: 99%